Granulocyte Therapy for Cancer - Wang, Dong (Science Insights, 2013)
GRANULOCYTE THERAPY FOR CANCER is the first book ever published dealing with the origin and development of the Granulocyte Therapy for Cancer. Dr. Zheng Cui has been regarded as “the father of cancer resistance super-mice”, made great contribution to the progress of Cancer Immunology and Immunotherapy. This book, based on his ten years’ research, intends to present a comprehensive overview from the serendipity discovery of the cancer complete resistant/ spontaneous regression (CR/SR) mice to the relevant cancer target killing mechanism mediated by leukocytes, as well as how the innovative therapeutic approach, Leukocyte Infusion Therapy (LIFT) applicable to human cancer.